2015
DOI: 10.4172/2329-6488.1000181
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies as a Predictors of Psychological Distress and Post Traumatic Growth among Flood Affected Individuals

Abstract: The aim of the present study was to see the predictive role of coping strategies in psychological distress and Post Traumatic Growth among 1862 individuals exposed to floods 2010 in Pakistan. The age range of the participants was 15 to 66 years (M = 28.25, SD = 9.59), with participation of both men and women. Data was collected during mid-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…However, by critically reviewing the studies, it is indicated that Help seeking behaviour related with the development of PTG and they do occur in different genders after any natural disasters Studies results are inconsistent for gender difference in PTG as most studies found no significant gender difference (Aslam & Kamal, 2015;Bianchini et al, 2017;García et al, 2014;Mordeno et al, 2016;Siqveland et al, 2015). Studies which were done on flood or tsunami did not find any gender difference even if the time of assessment was one month or after two to three years of the disaster (Aslam & Kamal, 2015;Mordeno et al, 2016;Siqveland et al, 2015). However, studies done on earth quake https: //doi.org/10.15405/epsbs.2019.05.02.1 Corresponding Author: Sadaf Alamdar Selection and peer-review under showed inconsistent results for gender differences.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, by critically reviewing the studies, it is indicated that Help seeking behaviour related with the development of PTG and they do occur in different genders after any natural disasters Studies results are inconsistent for gender difference in PTG as most studies found no significant gender difference (Aslam & Kamal, 2015;Bianchini et al, 2017;García et al, 2014;Mordeno et al, 2016;Siqveland et al, 2015). Studies which were done on flood or tsunami did not find any gender difference even if the time of assessment was one month or after two to three years of the disaster (Aslam & Kamal, 2015;Mordeno et al, 2016;Siqveland et al, 2015). However, studies done on earth quake https: //doi.org/10.15405/epsbs.2019.05.02.1 Corresponding Author: Sadaf Alamdar Selection and peer-review under showed inconsistent results for gender differences.…”
Section: Resultsmentioning
confidence: 99%
“…Only four studies correlated the demographic variable with the PTG. Two studies reported that being younger and with higher education are the two significant demographic variables for the PTG (Aslam & Kamal, 2015;Fergusson et al, 2015). However, Garcia et al (2014) & Siqveland et al (2015) reported no effect of age on PTG.…”
Section: Literature Search Strategymentioning
confidence: 99%
See 3 more Smart Citations